PTH-038 Cyanoacrylate injection therapy of small bowel varices by double-balloon enteroscopy (dbe): a tertiary centre experience. (17th June 2017) - Murino, A; Koukias, N; Vlachou, E; Planche, K; Patch, D; Despott, EJ
Abstract : Introduction: Small bowel varices (SBV) occur as a consequence of portal hypertension and may result in life-threatening mid-gut bleeding. First line management usually involves radiological intervention (RI) (e.g. TIPSS, stenting of occluded mesenteric veins +/- embolisation of culprit varices). In cases where RI is impossible, management options become very limited. This case series evaluated the usefulness of DBE facilitated cyanoacrylate injection of SBV. Method: Retrospective review of DBE facilitated cyanoacrylate injection of SBV at our institution (December 2015 to August 2016). Demographic, clinical, endoscopic and radiological findings, interventions and follow-up data were analysed. Results: Seven DBEs were performed in 5 patients (3 women, median age: 73 years). Four patients had previous surgery (hemi-hepatectomy (n=2); SB resection (n=2)); one patient had a history of intra-abdominal sepsis in childhood causing portal vein thrombosis. No radiological or surgical options were deemed feasible in any case. SBV were diagnosed at capsule endoscopy and triple phase CT mesenteric angiography. At DBE, a total of 10 nests of SBV were identified and injected with cyanoacrylate glue. There were no haemorrhagic or embolic complications but 1 patient developed an infection of a congenital urachal cyst, which was treated successfully with antibiotics. All patients underwent DBEs via the anterograde route and 1 patient required bi-directional DBE for treatment of both proximal and distal SBV and another patient required a 2 nd anterograde DBE for treatment of further patent proximal SBV. At 30 day follow-up post-therapy, only 1 patient had experienced a mild recurrence of mid-gut bleeding. Conclusion: Cyanoacrylate injection therapy of SBV at DBE appears to be a safe and effective management strategy for this condition when other first-line options are not feasible. Disclosure of Interest: A. Murino: None Declared, N Koukias: None Declared, E Vlachou Conflict with: Fujifilm and Aquilant Medical, K Planche: None Declared, D Patch: None Declared, E Despott Conflict with: Fujifilm and Aquilant Medical